THE INFLUENCE OF CONSUMER BEHAVIOR ON CONSUMER PURCHASE DECISIONS THROUGH BUYING INTEREST AND BUYING HABITS AS INTERVENING FACTORS - larbi el Hadi; Yunelly Asra (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2025)
This study aims to analyze the influence of consumer behavior on purchasing decisions with buying interest and buying habits as intervening variables at the local retailer A Bee Mart in Bengkalis. This study uses an associative quantitative approach with a survey method. The sample size was 100 respondents using a purposive sampling technique. Data collection was carried out through a questionnaire based on a Likert Scale of 1–5. Data analysis used SmartPLS version 4. The results showed that consumer behavior has a positive and significant effect on purchasing decisions, both directly and indirectly through intervening variables. The variable of buying interest proved to be a link that strengthens the relationship between consumer behavior and purchasing decisions, where consumers with positive perceptions of the product showed a higher intention to purchase. Meanwhile, buying habits also have an important role as a mediating variable, indicating that repeat purchases at A Bee Mart are triggered by positive experiences and consumer attachment to the store